The steal: a cultural history of shoplifting - Shteir, Rachel (Penguin Press, 2011)
A history of shoplifting assesses its cultural and economic significance, tracing its rise with the onset of department stores, its pathology, and its role as a symbol of anti-establishment sentiments and hyper-consumerism